Different reactive profiles of calmodulin in the CSF samples of Chinese patients of four types of genetic prion diseases - Jia, Xiao-Xi; Hu, Chao; Chen, Cao; Gao, Li-Ping; Liang, Dong-Lin; Zhou, Wei; Cao, Run-Dong; Xiao, Kang; Shi, Qi; Dong, Xiao-Ping (Frontiers in Molecular Neuroscience, 2024)
Background and purpose Calmodulin (CaM) levels exhibit significant elevation in the brain tissue of rodent and cell line models infected with prion, as well as in the cerebrospinal fluid (CSF) samples from patients diagnosed with sporadic Creutzfeldt-Jakob disease (sCJD). However, the status of CSF CaM in patients with genetic prion diseases (gPrDs) remains unclear. This study aims to assess the characteristics of CSF CaM in Chinese patients presenting four subtypes of gPrDs. Methods A total of 103 CSF samples from patients diagnosed with T188K-gCJD, E200K-gCJD, D178N-FFI, P102L-GSS were included in this study, along with 40 CSF samples from patients with non-prion diseases (non-PrDs). The presence of CSF CaM and 14-3-3 proteins was assessed using Western blots analysis, while levels of CSF 14-3-3 and total tau were measured using enzyme-linked immunosorbent assays (ELISAs). Statistical methods including multivariate logistic regression were employed to evaluate the association between CSF CaM positivity and relevant clinical, laboratory, and genetic factors. Results The positive rates of CSF CaM were significantly higher in cases of T188K-gCJD (77.1%), E200K-gCJD (86.0%), and P102-GSS (90.9%) compared to non-PrD cases (22.5%). In contrast, CSF CaM positivity was slightly elevated in D178N-FFI (34.3%). CSF CaM positivity was remarkably high in patients who tested positive for CSF 14-3-3 by Western blot and exhibited high levels of total tau (≥1400 pg/ml) as measures by ELISA. Multivariate logistic regression analysis confirmed a significant association between CSF CaM positivity and specific mutations in PRNP, as well as with CSF 14-3-3 positivity. Furthermore, the diagnostic performance of CaM surpassed that of 14-3-3 and tau when analyzing CSF samples from T188K-gCJD and E200K-gCJD patients. Conclusion Western blot analysis reveals significant variations in the positivity of CSF CaM among the four genotypes of gPrD cases, demonstrating a positive correlation with 14-3-3 positivity and elevated tau levels in CSF.